2002
DOI: 10.1029/2002jd002380
|View full text |Cite
|
Sign up to set email alerts
|

Mixing events revealed by anomalous tracer relationships in the Arctic vortex during winter 1999/2000

Abstract: [1] During the 1999/2000 Arctic winter SAGE III-Ozone Loss and Validation Experiment (SOLVE) campaign, high-resolution, in situ tracer data measured aboard the NASA ER-2 high-altitude aircraft revealed anomalous mixing events within the polar vortex. From January to March 2000 in the 350-500 K potential temperature range, we found mixing events during 15% of the flight time on average with significant maxima at potential temperatures of 450, 410, and 380 K. The events were spread throughout the vortex but show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
(53 reference statements)
2
24
0
Order By: Relevance
“…4). Indeed, Jost et al (2002) report a case where mixing across the vortex edge occurred at ≈380 K in early March of Arctic winter 2000 that did not noticeably change the O 3 /N 2 O relation. Esler and Waugh (2002) proposed to construct an artificial reference tracer from a linear combination of several longlived tracers so that a linear relation of a chemically active tracer with the artificial reference tracer would result.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4). Indeed, Jost et al (2002) report a case where mixing across the vortex edge occurred at ≈380 K in early March of Arctic winter 2000 that did not noticeably change the O 3 /N 2 O relation. Esler and Waugh (2002) proposed to construct an artificial reference tracer from a linear combination of several longlived tracers so that a linear relation of a chemically active tracer with the artificial reference tracer would result.…”
Section: Discussionmentioning
confidence: 99%
“…Based on high altitude aircraft measurements in the Arctic in early 2000, Rex et al (2002) and Jost et al (2002) demonstrated that mixing across the vortex edge leads to an increase in the mixing ratio of ozone for a given value of N 2 O. Further, Rex et al (2002) and emphasise that although in this winter mixing lines were observed, entrainment of extra-vortex air did not significantly alter the composition of the vortex air between January and March 2000.…”
Section: Observations Of Mixing Across the Vortex Edgementioning
confidence: 99%
See 2 more Smart Citations
“…There are also indications that we are able to reconstruct the small maximum denoted as E in Fig. 8, just before the dip, which has been identified as an intrusion of mid-latitude air by Jost et al (2002) and Konopka et al (2004). Table 1 summarizes the estimates of D based on roughness for N 2 O and O 3 , and checked by visual inspection, for all the flights of the SOLVE campaign from Kiruna.…”
Section: Analysis Of Solve Flightsmentioning
confidence: 99%